Effect Of Propylene Glycol On The Physical Preparation Of Katuk Leaf Ethanol Extract Herbal Syrup - Ellsya Angeline Rawar (Sean Institute, 2024)
Katuk has been used by the Indonesian citizen as a breast milk enhancer for breastfeeding mothers. People consume katuk in the form of decoction, herbal tea, or capsules. These preparations has a strong katuk taste and aroma. Preparation of ethanol extract of katuk leaves in herbal syrup has not been developed yet. The advantage of syrup is that it can cover unpleasant odors and aromas. Propylene glycol is an additional ingredients in the syrup which functions as a cosolvent which can increase solubility. The aim of this research was to determine the effect of propylene glycol on the physical preparation of katuk leaf ethanol extract herbal syrup. The herbal syrup formula for ethanol extract of katuk leaves contains katuk leaf extract, sucrose, anhydrous citric acid, methylparaben, propylparaben, glycerin, peppermint oil, distilled water, and propylene glycol with varying concentrations between 5-20%. The results of the research showed that extract yield of 10.6%. Katuk leaves extract ethanol contain flavonoids, phenolics, alkaloids, saponins, and tannins. The results of the physical preparation test of katuk leaf ethanol extract herbal syrup showed liquid form, green color, katuk leaf aroma, pH of around 6.16-6.20, specific gravity of around 1.1673-1.2523 g/mL, viscosity of around of 5.53-16.00 cPs, clarity, homogeneous, and displaced volume is 100 mL. The conclusion obtained is that the difference in propylene glycol composition does not affect the shape, color, aroma, pH, clarity, homogeneity, and displaced volume test. The greater the propylene glycol composition, the smaller the specific gravity and viscosity.